Boundary formation in the development of the vertebrate hindbrain. (25th January 2013) - Xu, Qiling; Wilkinson, David G.
Abstract The formation of a sharp interface of adjacent subdivisions is important for establishing the precision of tissue organization, and at specific borders it serves to organize key signaling centers. We discuss studies of vertebrate hindbrain development that have given important insights into mechanisms that underlie the formation and maintenance of sharp borders. The hindbrain is subdivided into a series of segments with distinct anteroposterior identity that underlies the specification of distinct neuronal cell types. During early stages of segmentation, cell identity switching contributes to the refinement of borders and enables homogenous territories to be maintained despite intermingling of cells between segments. At later stages, there is a specific restriction to cell intermingling between segments that is mediated by Eph receptor and ephrin signaling. Eph–ephrin signaling can restrict cell intermingling and sharpen borders through multiple mechanisms, including the regulation of cell adhesion and contact inhibition of cell migration. WIREs Dev Biol 2013, 2:735–745. doi: 10.1002/wdev.106 For further resources related to this article, please visit the WIREs website.